Modelling the obstacles to using bicycle sharing systems in the Tehran metropolis: A structural analysis - Akbari, Majid; Zarghamfard, Moslem; Hajisharifi, Arezoo; Entekhabi, Shahram Amir; Goodarzipour, Sadrallah (Quaestiones Geographicae, 2022)
The main objective of the current research is to identify and prioritise the obstacles to using bicycle sharing systems (BSSs) in the Tehran metropolis. The methodology of this research is analytical-descriptive and it aims to achieve applied goals. To do so, firstly the obstacles are identified through studying the theoretical and practical foundations of the issue and then by delving into factors associated with BSSs in the Tehran metropolis, extracting them through the content validity method. Then, the interrelations among the specified obstacles and their impact and effectiveness are determined through structural and MICMAC modelling. The data collection tool employed in the research assumes the forms of a survey and a face-to-face interview. According to the results, the following variables are among the ones associated with obstacles having the maximum impact on other obstacles: the financial problems and the disparity within the municipal management, culturalisation, educational shortage and negligence in using the participatory capacities of civilians. Before executing and taking any other strategy to overcome the obstacles, the forthcoming model supports Tehran metropolis municipal managers to identify the existent obstacles of the field in order to enable them to utilise a suitable approach as to lodging BSSs.